Integrated crop-livestock systems—A key to sustainable intensification in Africa - Duncan, Alan J.; Tarawali, Shirley A.; Thorne, Peter J.; Valbuena, Diego; Descheemaeker, Katrien K.; Homann-Kee Tui, Sabine (2013)
Mixed crop-livestock systems provide livelihoods for a billion people and produce half the world’s cereal and around a third of its beef and milk. Market orientation and strong and growing demand for food provide powerful incentives for sustainable intensification of both crop and livestock enterprises in smallholders’ mixed systems in Africa. Better exploitation of the mutually reinforcing nature of crop and livestock systems can contribute to a positive, inclusive growth trajectory that is both ecologically and economically sustainable. In mixed systems, livestock intensification is often neglected relative to crops, yet livestock can make a positive contribution to raising productivity of the entire farming system. Similarly, intensification of crop production can pay dividends for livestock and enhance natural resource management, especially through increased biomass availability. Intensification and improved efficiency of livestock production mean less greenhouse gases per unit of milk and more milk per unit of water. This paper argues that the opportunities and challenges justify greater investment in research for development to identify exactly where and how ‘win-win’ outcomes can be achieved and what incentives, policies, technologies and other features of the enabling environment are needed to enable sustainable, integrated and productive mixed crop-livestock systems.